2019
DOI: 10.1007/s13365-019-00775-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma (1 → 3)-β-d-glucan and suPAR levels correlate with neurocognitive performance in people living with HIV on antiretroviral therapy: a CHARTER analysis

Abstract: Despite antiretroviral therapy (ART), people living with HIV (PLWH) have higher rates of non-AIDS disorders, such as neurocognitive (NC) impairment (NCI) than the general population. (1-3)-β-D-Glucan (BDG) is a fungal cell wall component which serves as a biomarker for gut barrier integrity failure and microbial and fungal translocation. The primary objective of this study was to determine whether higher plasma and cerebrospinal fluid (CSF) levels of BDG and suPAR were associated with NCI in PLWH. Paired blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 37 publications
0
38
1
Order By: Relevance
“…Bacteria and fungi are the two most abundant populations of the gut microbiome. While bacterial translocation has been a focus of HIV research for a number of years, fungal translocation recently came into focus as a driver of immune activation, persistent inflammation, and non-AIDS events (7)(8)(9)(10)(11)(12). A review included in this supplement evaluated recent literature to untangle the respective roles of circulating lipopolysaccharide (LPS) and (1->3)-B-D-Glucan (BDG), which are major components of bacterial and fungal cell walls respectively and established biomarker of bacterial and fungal translocation (Ramendra et al).…”
Section: Hiv-associated Immune Activation and Persistent Inflammationmentioning
confidence: 99%
“…Bacteria and fungi are the two most abundant populations of the gut microbiome. While bacterial translocation has been a focus of HIV research for a number of years, fungal translocation recently came into focus as a driver of immune activation, persistent inflammation, and non-AIDS events (7)(8)(9)(10)(11)(12). A review included in this supplement evaluated recent literature to untangle the respective roles of circulating lipopolysaccharide (LPS) and (1->3)-B-D-Glucan (BDG), which are major components of bacterial and fungal cell walls respectively and established biomarker of bacterial and fungal translocation (Ramendra et al).…”
Section: Hiv-associated Immune Activation and Persistent Inflammationmentioning
confidence: 99%
“…Besides disruption of the mucosal barrier (eg caused by persistent inflammation, hypoperfusion or oxidative stress), major risk factors for fungal translocation also include alteration of the normal GI microflora and impaired host defence 109. Multiple different underlying diseases that are associated with one of these conditions may contribute to fungal translocation, including sepsis,110,111 kidney disease, liver cirrhosis 112 and HIV infection [113][114][115][116][117]. The effects of chemotherapy on fungal organisms themselves have been theorised to also play a role in translocation.…”
mentioning
confidence: 99%
“…Circulating BDG is currently used for the clinical diagnosis of Candida, Aspergillus, and Pneumocystis jirovecii invasive infections [18]. Recently, we and others have found that plasma levels of BDG are associated with epithelial gut damage and risk of developing inflammatory non-AIDS comorbidities in PLWH without invasive fungal infection (IFI) [12][13][14][18][19][20][21][22]. These findings show converging evidence that BDG is a clinically significant fungal translocation marker in PLWH.…”
Section: (1→3)-β-d-glucan (Bdg) Is a Major Component Of Most Fungal Cmentioning
confidence: 87%
“…LPS is a bacterial cell wall polysaccharide and is a well-known inducer of innate immune activation [11]. Besides bacterial translocation, there is increasing awareness regarding fungal translocation [12][13][14][15]. Fungi contribute greatly to opportunistic infections in PLWH, including Pneumocystis jirovecii in the respiratory tract and Candida albicans in the gastrointestinal tract [16].…”
mentioning
confidence: 99%